Diabetes Self-Care in Older Adults With Type 1 Diabetes Mellitus: How Does Cognition Influence Self-Management - Taboada Gjorup, Ana Lúcia; Snoek, Frank J.; van Duinkerken, Eelco (Frontiers in Clinical Diabetes and Healthcare, 2021)
With increasing knowledge and improvements in options for glycemic control, the life-expectancy of patients with type 1 diabetes mellitus (T1DM) has increased considerably over the past decades. Whereas this is undeniably positive for patients, aging is related to natural decline in cognitive functions. As patients with T1DM across the life-span are susceptible to cognitive deterioration, an interaction with aging may be expected and the risk of development of dementia might be increased. As achieving glycemic control depends on a set of diabetes self-management behaviors, it is imperative to understand how cognitive functions are involved in the upkeep of these behaviors and how cognitive impairment may affect them. In this narrative review, we set out to understand the relationship between cognition and T1DM self-care by first reviewing the glycemic targets in older adults, what treatment options are available, and what cognitive functions they draw upon. We will then review the cognitive literature in older adults that is available and then link both together. Lastly, we finish with clinical recommendations and suggestions for future research.